Presentation of Two Cases with Early Extracranial Metastases from Glioblastoma and Review of the Literature. (9th May 2016) - Johansen, Maria Dinche; Rochat, Per; Law, Ian; Scheie, David; Poulsen, Hans Skovgaard; Muhic, Aida
Abstract : Extracranial metastases from glioblastoma are rare. We report two patients with extracranial metastases from glioblastoma. Case 1 concerns a 59-year-old woman with multiple metastases that spread early in the course of disease. What makes this case unusual is that the tumor had grown into the falx close to the straight sinus and this might be an explanation to the early and extensive metastases. Case 2 presents a 60-year-old man with liver metastasis found at autopsy, and, in this case, it is more difficult to find an explanation. This patient had two spontaneous intracerebral bleeding incidents and extensive bleeding during acute surgery with tumor removal, which might have induced extracranial seeding. The cases presented might have hematogenous spreading in common as an explanation to extracranial metastases from GBM.